2020
DOI: 10.9734/ajess/2020/v7i230195
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Teachers on School-Based Factors Influencing Absenteeism of Students in Public Secondary Schools in Central Senatorial District of Ondo State, Nigeria

Abstract: The study investigated the perception of teachers on school-based factors influencing absenteeism of students in Public Secondary Schools in Central Senatorial District of Ondo State, Nigeria. It adopted descriptive-survey design, raised 3 questions and formulated 2 hypotheses to achieve this feat. Data were collected from 150 government appointed and full time teachers, drawn from 15 Public Secondary Schools in the District. Instrument used was a questionnaire, validated and tested for reliability (α=0.82). D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…The chi-square tests done in this study also reveal statistically significant relationships between nurse educators' attitudes and various factors. This aligns with the results in the literature which observed that there exist a statistically significant association between the academic performance of students and the instructional communication abilities of educators (Matthew, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…The chi-square tests done in this study also reveal statistically significant relationships between nurse educators' attitudes and various factors. This aligns with the results in the literature which observed that there exist a statistically significant association between the academic performance of students and the instructional communication abilities of educators (Matthew, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, other former studies [14], [33], [41] found that public enlightenment (a tool for awareness) is an effective strategy for attracting students to technical and vocational education. An increasing decline of student enrolment in any educational programme calls for concerted efforts particularly from the administrators of the programme [12], [42], [43]. Therefore, attracting strategies must be focused, calculated and purpose driven in order to achieve the target goals.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the activities of teachers and pupils cannot develop beyond the cognizance of the heads. Different countries such as the United States of America (USA), Canada, Australia, Brazil, New Zealand, Uganda, Thailand, Argentina, Mexico, Qatar, Kenya, Iran, Indonesia, Senegal, all are experimenting SBMCs but with different objectives (Matthew, 2020). The researchers observed that public primary schools in Maiduguri Metropolis are faced with dwindling pupils' achievement which could be attributed to a factors like poor management of the system, supervision and monitoring of teachers and pupils maintenance of discipline, inadequate provision of educational resources, and poor maintenance, of the resources, there is no gainsaying that proper management and effective administration are the kingpin for efficiency of educational process in Maiduguri Metropolis, Borno State.…”
Section: Introductionmentioning
confidence: 99%